Effect of habitat on breeding success and fledging age in Oystercatchers (Haematopus ostralegus) breeding in the south, west, and Westfjords of Iceland - Carroll, Jamie Noreen, 1995- (2020)
Verkefnið er lokað til 17.06.2021. Iceland is a globally important breeding area for a variety of ground-nesting wader species. This includes Eurasian Oystercatchers (Haematopus ostralegus), which are unique waders in that they: hatch semi-precocial chicks dependent on parental feeding, are partially migratory, and utilize both coastal and inland breeding territories. This system presents a unique opportunity to study the influences that differences in habitat quality have on breeding success and behavior of chicks. Little is known about patterns of habitat selection of wader species breeding in Iceland, or comparative breeding success of oystercatchers utilizing different habitats. This study identified and compared the breeding success and fledging age of oystercatchers breeding in different habitat types in the South, West, and Westfjords of Iceland. Additionally, provisioning data was obtained for the Westfjords region. The results show that productivity was influenced by habitat (p<0.001) and by region (p<0.001), and was higher in regions of predominantly coastal habitat use. Additionally, fledging success was influenced by habitat (p<0.001) and by region (p<0.01). Differences on predation rates and resource availability are most likely driving variances in reproductive success. Oystercatchers in the Westfjords increasingly fed their chicks small, coastal prey as chicks grew, which may also reflect an unavailability of terrestrial prey items, but provisioning studies should continue in the future to provide further information on resource use. Fledging age was similar across regions and habitat types, but more data is needed to explore this further. Understanding how oystercatchers are utilizing different resources, and how that might change and be translated into breeding success, is vital for understanding their population ecology and effectively contributing to management decisions of important bird areas.